Levensteiniella manusensis sp. nov., a new polychaete species (Annelida: Polynoidae) from deep-sea hydrothermal vents in the Manus Back-Arc Basin, Western Pacific - Wu, Xuwen; Xu, Kuidong (Zootaxa, 2018)
A new species belonging to the subfamily Macellicephalinae (Annelida: Polynoidae), Levensteiniella manusensis sp. nov., is described based on material collected from deep-sea hydrothermal vents in the Manus Back-Arc Basin. The new species is readily distinguished from the congeners by having two pairs of ventral papillae on segments 11 and 12, the first pair of which is distally dichotomous. Levensteiniella manusensis is also characterized by the combination of the notochaetae which are smooth or serrated on the curved side, and the elytra with micro- and macropapillae on the surface and thickened bulbous projections on the posterior border. Based on morphological comparisons of the main features, we provide two keys to six species of Levensteiniella described to date based on males and females respectively.